OPTIMALISASI PEMBELAJARAN SEJARAH DENGAN PENERAPAN METODE ACTIVE DEBATE - Dyah Kumalasari (ISTORIA: Jurnal Pendidikan dan Sejarah, 2008)
Abstract  This research is intended to solve the problem of optimizing the application of active debate method to improve of learning quality of History Reflection subject at the History Education Department of Social Science and Economics Faculty of the State University of Yogyakarta. The research is designed as a classroom action research, applied to the sixth semester students, from January to July of the 2006 academic year. The research is conducted in two cycles of actions through four stages: the stage I and II encompassing the First Diagnostic and Therapy stage, and the stage III and stage IV constituting the Repeated Diagnostic and Therapy Stage. The data of study were collected by means of observations and interviews as well as evaluation of the quality of discussing skills with the grading scores of 1, 2, 3, and 4, and the data obtained were then analyzed using a t-test. Findings of the classroom action research through optimizing the application of the active debate method to the learning process of History Reflection subject show the significant improvement in learning process and achievement. Qualitatively, the quality of learning process increase significantly and quantitatively the learning achievement improved the averaged achievement of 2,3. Therefore, the research has been able to increase the averaged achieved score of 79,6, with a t-coefficient of 2,89344047 at the level of significance of 1% (very significant). Keywords: Active Debate Method, Historical Learning, Learning Quality